The relationship between square dance exercise and quality of life in middle-aged and older adults: chain mediated effects of negative emotions and attitudes toward aging - Ting Ouyang; Ting Ouyang; Yujia Qu; Xinyu Du; Ming Fan; Yan Wang (Frontiers Media S.A., 2024)
BackgroundWith the continuous development of society and the economy, population aging has become an inevitable global development trend, triggering a series of social problems and having a more serious impact on the physical and mental health of middle-aged and older adults. Physical exercise is one of the key factors for improving the overall health and quality of life of individuals, but the role of square dance exercise and the quality of life of middle-aged and older adults have not yet been clarified.PurposeThis study aimed to investigate the associations between square dance exercise and the quality of life of middle-aged and older adults and its mechanism of action, including its effects on physical health and mental health, with negative emotions and attitudes towards aging as mediating variables.MethodThis study adopted a cross-sectional research method, using the Physical Activity Rating Scale (PARS-3), Depression-Anxiety-Stress Scale in Simplified Chinese (DASS-21), Attitudes toward Aging Questionnaire (AAQ), and 12-item Short Form of the Health Survey (SF-12), and launched an online survey on the QuestionStar platform from August-September 2023 for 4,636 middle and older adults aged 45-74 years. The survey results were analyzed via Pearson correlation analysis via SPSS 27.0 and structural equation modeling analysis via Mplus 8.3 to test the model fit and mediation effects.ResultsSquare dance exercise was significantly correlated with negative emotions, attitudes towards aging, and quality of life (r = −0.042-0.878, p < 0.01). Square dance exercise significantly and positively predicted quality of life (β = 0. 202, p < 0.001). Negative emotions and attitudes towards aging are chain mediators of square dance exercise and quality of life, and the mediation consists of three pathways: separate mediation of negative emotions, separate mediation of attitudes towards aging, and chain mediation of negative emotions-attitudes towards aging.ConclusionThis study is dedicated to deepening the scientific role of how square dancing, as a health-promoting activity, can optimize the quality of life of middle-aged and older adults through the mediating mechanism of negative emotion alleviation and positive attitudes towards aging and then optimize the quality of life of middle-aged and older adults. This process not only enriches the theoretical framework of the complex interactions between psychosocial factors and healthy aging but also provides a solid empirical foundation for the development of health intervention strategies aimed at enhancing the overall well-being and quality of life of the middle-aged and older adults.